(3GdYdGbGJ GdYGeI aj GdbQf GdMGOj h GdYTQjf (B:s (3GdfXQjI h GdeeGQSI efMi fXGej h GSJQGJjLj (B/s - (3OQI, YHO GdHGQj GHQGgjes; (3GdeLGdj, fHjd Ndjas ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3eaGgje GdYdGbGJ GdYGeI(B- (3GdJMOjGJ GdJj JhGLg GdYdGbGJ GdYGeI aj GdbQf GdMGOj hGdYTQjf(B- (3eONdGJ fXGe GdYdGbGJ GdYGeI(B- (3YedjGJ fXGe GdYdGbGJ GdYGeI heNQLGJg(B- (3GdefMi GdESJQGJjLj ddYdGbGJ GdYGeI(B- (3GdJWHjb aj GdYdGbGJ GdYGeI(B- (3GdYdGbGJ GdYGeI aj bWGYGJ heDSSGJ eMOOI(B- (3bVGjG aj GdYdGbGJ GdYGeI GdeYGUQI(B.s
(3eQGLY U(B.439 (3;LOGhd U(B.4 (3; CTcGd U (B5s
Keywords: (3GdEJUGds; (3GdEOGQI GdYGeIs; (3GdYdGbGJ GdYGeIs; (3GdefXeIs